A study to evaluate the efficacy of instillation of ropivacaine with fentanyl, dexmedetomidine, or morphine through surgical drain for post-operative analgesia in patients undergoing modified radical mastectomy - Sumit Das; Pritam Yadav; Sanjay Johar; Naveen Malhotra; Irin Saha; Ritu Rathee (Asian Journal of Medical Sciences, 2023)
Background: Local anesthetics have become vital part of multimodal analgesia approach. Instillation of local anesthetics through surgical drain is easier and safer method than conventional nerve blocks. Various local anesthetic drugs and adjuvants have been used for post-operative pain management through surgical drains. Aims and Objectives: This study was conducted to evaluate the efficacy of instillation of ropivacaine with fentanyl, dexmedetomidine or morphine through surgical drain for post-operative analgesia and patient satisfaction in patients undergoing modified radical mastectomy. Materials and Methods: A prospective, randomized, and double-blind study was conducted dividing 75 female patients aged 30–70 years who underwent modified radical mastectomy into three groups: Group (RM) received 40 ml 0.25% ropivacaine with 4.5 mg morphine, group (RD) 40 ml 0.25% ropivacaine with 1 mg/kg dexmedetomidine and group (RF) 40 ml 0.25% ropivacaine with 50 microgram fentanyl, instilled through surgical drains. Results: Visual analog score for pain at rest and movement was significantly lower in group RM as compared to group RD and RF with no significant difference among group RD and RF at different time intervals postoperatively. Patient satisfaction at 24-h postoperatively was significantly better in group RM as compared to group RD and RF (P=0.01) with no significant difference among group RD and group RF. Conclusion: Instillation of ropivacaine with morphine provides good pain relief, prolonged duration of analgesia, and good patient satisfaction in the post-operative period as compared to ropivacaine with dexmedetomidine or fentanyl.